Molecular Dynamics Simulations Provide Insights into Structure and Function of Amadoriase Enzymes - Federica Rigoldi; Ludovica Spero; Andrea Dalle Vedove; Alberto Redaelli; Emilio Parisini; Alfonso Gautieri (Innovative Biosystems and Bioengineering, 2017)
Background. Enzymatic assays based on Fructosyl Amino Acid Oxidases (FAOX) represent a potential, rapid and economical strategy to measure glycated hemoglobin (HbA1c), which is in turn a reliable method to monitor the insurgence and the development of diabetes mellitus. However, the engineering of naturally occurring FAOX to specifically recognize fructosyl-valine (the glycated N-terminal residue of HbA1c) has been hindered by the paucity of information on the tridimensional structures and catalytic residues of the different FAOX that exist in nature, and in general on the molecular mechanisms that regulate specificity in this class of enzymes.